Left atrial pressure and predictors of survival after percutaneous mitral paravalvular leak closure. Issue 5 (14th July 2017) - Maor, Elad; Raphael, Claire E.; Panaich, Sidakpal S.; Alkhouli, Mohamad; Cabalka, Allison; Hagler, Donald J.; Pollak, Peter M.; Reeder, Guy S.; Eleid, Mackram F.; Rihal, Charanjit S.
Abstract: Background: Data on the clinical utility of left atrial (LA) hemodynamic monitoring during percutaneous mitral interventions are limited. Objectives: To evaluate the association between intraprocedural LA pressures during percutaneous mitral paravalvular leak (PVL) closure and long term survival. Methods: Patients who underwent mitral PVL repair with invasive LA pressure monitoring were divided at baseline to three tertiles based on their mean final LA pressure (<25%; 25‐30%; >30% of mean systolic blood pressure). Primary outcome was all‐cause mortality. Results: 134 patients (mean age 68 ± 12 years) were studied. Over 3 year mean follow‐up, 81 (38%) patients died. The cumulative probability of death at 3 years was significantly higher among patients in the highest LA pressure tertile (56 ± 8% vs. 28 ± 5%, log rank P  < 0.001). More than mild residual mitral regurgitation (MR) by transesophageal echocardiography (TEE) was associated with a 2.5‐fold increased risk of death and patients in the highest LA pressure tertile had 2.2‐fold higher mortality ( P  < 0.001 and = 0.003 respectively). After adjustment for residual MR by TEE, each 10% acute procedural reduction in LA pressures was associated with a significant 9% reduced risk of death ( P  = 0.023). Multivariate Cox regression with adjustment for multiple predictors of death showed that patients in lower LA pressure tertiles had 59% lower mortality ( P  = 0.003). Conclusion: Lower LA pressure following mitral PVL closure is an independent predictor of improved survival, even after adjustment for residual MR. LA pressure monitoring may be a useful tool for procedural guidance during mitral PVL closure.